Strategies for Enhancing Zakat Fund Management in Minority Areas: a Case Study in Humbang Hasundutan Regency - Jhon Anwar Tumanggor; Yayat Sujatna (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2023)
This study focuses on analyzing two key aspects: zakat collection strategies and the effectiveness of zakat management in Islamic minority regions, particularly in Humbang Hasundutan Regency. Employing a descriptive method with a quantitative approach, the analysis of zakat collection strategies utilizes the SWOT technique, while the effectiveness of zakat management is assessed through the ZCP 10-point instrument, specifically targeting Disbursement Management. The findings indicate that the Zakat Collection Unit (UPZ) of BAZNAS in Humbang Hasundutan falls within the "growth and build" category, with weighted scores of IFAS and EFAS being 2.44 and 3.13, respectively. This suggests an adoption of an aggressive growth-oriented strategy. Recommended strategies to enhance zakat collection include market penetration, innovation in culturally-based zakat programs like Batak Danilhan Natolu, universal philanthropy programs, utilization of information technology, and institutional strengthening. The effectiveness of zakat management by UPZ Baznas Humbang Hasundutan increased quantitatively from 73.83% in 2019 (effective) to 97.39%-104.79% in 2020-2022 (highly effective). Qualitatively, zakat management is deemed highly effective in the ZCP Point 10 category